Residues of diflubenzuron on horse chestnut (Aesculus hippocastanum) leaves and their efficacy against the horse chestnut leafminer, Cameraria ohridella - Nejmanová, Jana; Cvacka, Josef; Hrdý, Ivan; Kuldová, Jelena; Mertelík, Josef; Muck, Alexander; Nesnerová, Petra; Svatos, Ales (Pest management science, 2006)
Residues of the insect growth regulator diflubenzuron were quantified on horse chestnut (Aesculus hippocastanum L.) leaves treated with a diflubenzuron 480 g litre(-1) SC, Dimilin. To analyse the samples, an analytical procedure was developed involving a simple extraction step followed by high-performance liquid chromatography on an octadecyl-modified silica column with methanol + 0.01 M ammonium acetate mobile phase. The results showed diflubenzuron to be highly stable on horse chestnut leaves; more than 4 months (127 days) after application, 38% (on average) of the insecticide still remained on/in the leaves. The data confirmed biological observations showing diflubenzuron's long-term efficacy against the horse chestnut leafminer, Cameraria ohridella Deschka and Dimić, which is the most important pest of the horse chestnut in Europe. The hypothesis of possible penetration of diflubenzuron into the leaf mass is explored and discussed.
Keywords: listy rostlin; Moths; diflubenzuron; rezidua pesticidů; Animals; Pesticide Residues; Drug Stability; stabilita léku; Aesculus; Diflubenzuron; zvířata; můry; Plant Leaves